Maker: the return of the builders. A possible digital transition for Architecture - Sergio Pone (Agathón)
This contribution attempts to answer the following question: how will the digital revolution affect architecture in the near future? To try to formulate a convincing answer, only very faint signals that come from courageous experiments are available, a result mainly of research work rather than market-proposed stimuli. A handful of researchers in a select number of Universities, armed with extraordinary digital skills and maker-type instrumentation, are creating new experimental constructions in which highly complex design is combined with extremely simple construction, which do not require the manufacturing skills and expensive equipment that populate traditional construction sites. By establishing these lines of development, it would be possible to bring architecture close to the people and restore a central role for the designer in the making of buildings.